A unification-based approach to configure generic protocols into agent interaction models. (3rd December 2009) - Quenum, Jose Ghislain; Aknine, Samir
This paper presents a new approach for generic protocol configuration in agents' internal models. Generic protocols are reusable predefined sequences of message exchanges. Their specifications are most of the time merged with the internal architecture of agents. This requires designers to introduce them by hand every time it is needed. It results in inconsistencies that may occur in message exchange at run time. Inconsistent message exchange in turn results in the failure of the associated interaction. First, we introduce a new language to specify generic protocols. Then we generate the interaction model of agents using their functional model, a generalisation of the design model (only the part devoted to interaction). In order to generate the interaction model, we developed a unification mechanism to automatically check the compliance of a protocol specification with the elements of a functional model. We argue that our approach guarantees that the implementation of the interaction model complies with the initial specification of the protocols it is based on. Here, we discuss the knowledge and reasoning mechanism involved in our approach. An implementation of our approach is also discussed. Particularly, we show the approach's effectiveness with real-world and complex applications.